Subjectivity in Kurt Cobain's songs “Come as you are”, “Stay Away”, “All apologies” : the use of metaphors and metaphorical expressions alluding to the construction of identities - Corso, Noelia del Valle (2024)
Fil: This Final Research Paper (FRP) employs hermeneutics to show how metaphors and metaphorical expressions are used by Kurt Cobain, the singer and songwriter of the rock band “Nirvana”, making allusions to Subjectivity’s construction, i.e.: how identity is constructed. In order to do so, this FRP draws on the theoretical framework given by authors dealing with Language and Power, mainly from the viewpoints of Fairclough (1989), Gadamer (1975), Nietzche (2012), Mouffe (1999), Skinner (2007) and Lotman (1995), who also make reference to how Subjectivity is constructed. By analyzing selected lyrics written and composed by Kurt Cobain, this study reveals that Cobain's compositions encode how identities are constructed. Moreover, this research contributes to our understanding of the role of language in shaping identities, a concept known as Subjectivity. Finally, this FRP will be held following Gadamer’s (1975) idea that there is not a univocal view or final interpretation of any text.